A Literature Review Evaluation Of Hospital Information Management System (SIMRS) Based On Human Organization Technology-Fit (Hot-Fit) Method - Widiyanti, Ayu Tri; Andriyanto, Arief (NHM PRESS, 2024)
SIMRS is a series of activities that cover all hospital health services at all administrative levels which can provide information to managers for the management process. The aim of this literature review is to analyze the success of implementing the SIMRS hospital management information system. The method used in this literature review uses a comprehensive strategy, such as searching for articles in research journal databases, searching via the internet, reviewing articles. Data collection was carried out using secondary data which is support sourced from various existing literature and references. Data analysis was carried out using literature review techniques including looking for similarities (compare), looking for differences (contrast), giving views (critite), comparing (synthesize), and summarizing (summarize). Database searches used included SciVerse ScienceDirect, Scopus, Pubmed and Google scholar. The keywords used in the article search were SIMRS, SOP, Evaluation Monitoring, Information Management. 457 articles were obtained, then the reviewers screened the titles and abstracts to obtain 10 articles that were appropriate to the topic and carried out a review. appropriate through analysis of objectives, suitability of topics, research methods used, sample size, research ethics, results of each article, as well as limitations that occur. There are effective results in hospital services with a variety of service management information systems and different features. There is a need for regulations and minimum standardization that must be determined by the Ministry of Health in order to achieve uniform services and be able to carry out full electronic-based activities. There is a need for the capacity of the Ministry of Health to provide applications for hospitals that are still unfamiliar with SIMRS and ongoing training and need more monitoring.